2002
DOI: 10.1007/s00221-002-1101-1
|View full text |Cite
|
Sign up to set email alerts
|

Effort-induced mirror movements

Abstract: During sustained, fatiguing maximal voluntary contraction of muscles of one hand, muscles of the other hand gradually become activated also. Such effortinduced mirror movements indicate a decreased ability of the central nervous system (CNS) to selectively control individual muscles. We studied whether altered transcallosal inhibition (TCI) contributed to this phenomenon. TCI was determined in ten healthy subjects by measuring the ipsilateral silent period (iSP) and the contralateral silent period (cSP) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…For example, some studies have reported “motor irradiation” or activation of homologous muscles of the other hand when performing various types of contractions in healthy adults (Aranyi and Rosler, 2002, Shinohara, et al, 2003). Thus, after unilateral motor cortex damage the contralesional hemisphere loses some excitation as well as inhibition due to (Carson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies have reported “motor irradiation” or activation of homologous muscles of the other hand when performing various types of contractions in healthy adults (Aranyi and Rosler, 2002, Shinohara, et al, 2003). Thus, after unilateral motor cortex damage the contralesional hemisphere loses some excitation as well as inhibition due to (Carson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that motor overflow is due to insufficient interhemispheric inhibition via the corpus callosum. [17][18][19] Better movement quality of females could be interpreted in two ways: first, the female brain is more capable of inhibitory processes; second, this interhemispheric inhibition is a maturational process, and females are advanced by almost 2 years in bone age and puberty. To address this, the current researchers analyzed contralateral AMs for a group of adults (n=145) at ages 45 to 55 years and found no sex difference (p=0.47).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, if the muscles of the active limb are progressively fatigued, there is a corresponding increase in the EMG activity recorded from the opposite limb (Arányi and Rösler, 2002). These data are consistent with the proposal that the extent of irradiation to the opposite limb is contingent upon the level of neural drive directed to the muscles engaged in the focal movement (Todor and Lazarus, 1986).…”
Section: Cross Activationmentioning
confidence: 99%